HOTS-Based e-evaluation Quizwhizzer in science learning in elementary schools - Farida Nur Kumala; Intan Safitri; T. Triwahyudianto; Arnelia Dwi Yasa; Moh Salimi (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
Teachers have’nt implemented HOTS-based questions for learning evaluation, resulting in students' low thinking abilities. This research aims to develop HOTS-based E-evaluation using the Quizwhizzer application. This research uses the ADDIE model with various stages, namely (1) the analysis stage, curriculum analysis, student character, and learning evaluation are carried out; (2) the design stage, learning materials are determined, HOTS questions and research instruments are prepared; (3) the development stage, validation of the suitability of the material, language and media is carried out; (4) the implementation stage, a validation test of the practicality and effectiveness of the application is carried out; (5) the final, evaluation stage was carried out to find out deficiencies in the application. The research subjects were 28 class IV students at SDN Mulyorejo 3. The instruments used are tests and questionnaire sheets. The research results showed that the E-Evaluation of the feasibility test was 90 percent from material experts, 96 percent from language experts, and 92 percent from media experts. The results of teacher practicality were 95 percent, students were 92 percent and effectiveness showed that there was an increase in students' HOTS abilities.